Racial legacies Jung, politics and culture - Brewster, Fanny; Morgan, Helen (Routledge, Taylor & Francis Group, 2022)
"This essential new book presents a discussion of racial relations, Jungian psychology, and politics as a dialogue between two Jungian analysts of different nationalities and ethnicities, providing insight into a previously unexplored area of Jungian psychology"--
"Routledge Focus"--from cover
Keywords: Jung, C. G. -- 1875-1961; Rassismus; Tiefenpsychologie; Analytische Psychologie; Race relations / Psychological aspects; Jungian psychology; Relations raciales / Aspect psychologique; Psychologie analytique